A normal totalitarian society : how the Soviet Union functioned and how it collapsed - Shlapentokh, Vladimir 1926-2015 (M. E. Sharpe, 2001)
Theoretical concepts -- Two components of Soviet ideology: socialism and Russian nationalism -- Adjusting the revolutionary ideology to totalitarian goals -- World revolution as a geopolitical instrument -- Open and closed ideologies -- Policy toward key social groups: workers and creative intelligentsia -- The political system: the supreme leader as the major institution -- An effective political machine -- The economy: organic flaws and achievements -- Public opinion: acceptance of the regime -- The regime and the empire: a complex relationship -- Reforms: alternatives in history -- Reforming the system, destroying its fundamentals -- Consequences